2018
DOI: 10.1038/s41598-018-28505-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the expression of cluster of differentiation (CD)39 and CD73 between propofol- and sevoflurane-based anaesthesia during open heart surgery

Abstract: High expression of cluster of differentiation (CD)39 and CD73 has cardio-protective effects. We hypothesised that the expression of CD39 and CD73 would differ between propofol- and volatile anaesthetic-based anaesthesia in patients undergoing open heart surgery (OHS). The objective of this prospective randomized trial was to compare the changes in CD39 and CD73 levels in CD4+ T cells between propofol- and sevoflurane-based anaesthesia during OHS. The study randomly allocated 156 patients undergoing OHS to a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…The evidence of a stronger perioperative effect of IL-10 on circulating monocytes in the Propofol group is also supported by the presence of higher Propofol-induced variations of the first sextile-based HLA-DR low fractions, in particular at T2 and T4. These preliminary flow cytometric monocyte-derived data seem to be in accord with previous clinical observations demonstrating both a higher systemic anti-inflammatory effect, during and after CPB surgery, of a Propofol-based anesthesia in comparison with Sevoflurane, 21,22 and a Propofol dose-dependent induction of IL-10 plasma release during CPB. 23…”
Section: Discussionsupporting
confidence: 90%
“…The evidence of a stronger perioperative effect of IL-10 on circulating monocytes in the Propofol group is also supported by the presence of higher Propofol-induced variations of the first sextile-based HLA-DR low fractions, in particular at T2 and T4. These preliminary flow cytometric monocyte-derived data seem to be in accord with previous clinical observations demonstrating both a higher systemic anti-inflammatory effect, during and after CPB surgery, of a Propofol-based anesthesia in comparison with Sevoflurane, 21,22 and a Propofol dose-dependent induction of IL-10 plasma release during CPB. 23…”
Section: Discussionsupporting
confidence: 90%
“…Inhaled sevoflurane in contrast provides sufficient sedation during PP and fast awakening that allows the patient to actively participate in his therapy and recovery. Besides a well-controllable sedative effect, sevoflurane provides a number of side effects that seem to be beneficial for the treatment of patients with CARDS [35][36][37]: These include bronchodilating [38], anti-inflammatory [39] and, in theory, cardioprotective effects [40,41]. However, cardioprotective effects have not yet been clinically demonstrated [42].…”
Section: Clinical Significancementioning
confidence: 99%
“…Furthermore, regulator T cells, tumor-associated macrophages and myeloidderived suppressor cells (MDSCs) recruited by cancer cells also favor tumor progression (22). Propofol attenuated the decrease in CD39 and CD73 in circulating CD4+ T cells compared to sevoflurane-based anesthesia in patients undergoing open heart surgeries (23), while similar comparative studies have not been reported in breast cancer patients despite that circulating regulatory T cells has been recently reported to be significantly increased in breast cancer patients which may impact on the stage and histological type of breast cancer (24). The possible mechanisms of propofol and sevoflurane on anticancer immunity, breast cancer cell proliferation, migration and apoptosis are summarized in Figures 1 and 2.…”
Section: Immune Pathogenesis Of Tumorigenesismentioning
confidence: 99%